Ultrasound assisted green protocol for the synthesis of quinoxaline based bisspirooxindoles: crystal structure analysis, enone umpolung, DFT calculations, anti-cancer activity, and molecular docking studies - Baddepuri, Sravanthi; Allaka, Bhargava Sai; Gamidi, Rama Krishna; Faizan, Mohmmad; Pawar, Ravinder; Basavoju, Srinivas (Synthetic Communications, 2023)
A series of novel quinoxaline based bisspirooxindolo-pyrrolizidines were synthesized through 1,3-dipolar cycloaddition under ultrasonication with shorter reaction time and good yields. The compounds were well characterized by various spectroscopic methods and finally single crystal X-ray diffraction method (4c, 4d). DFT energy calculations confirm the regioselectivity due to enone umpolung effect. The in vitro anti-cancer activity of the synthesized compounds (4a-s) shows that the compounds 4g and 4q exhibited good anti-cancer activity with IC50 values14.51 +/- 1.1 and 11.36 +/- 0.23 mu M against DU-145 prostate cancer cell line; and 16.78 +/- 0.95 and 14.28 +/- 0.64 mu M against Hela cervical cancer cell lines when compared to the standard anti-cancer drug doxorubicin (1.75 +/- 0.06 and 1.35 +/- 0.09 mu M). In silico molecular docking studies indicated that the synthesized compounds may serve as a potential lead for the further development of novel anti-cancer agents.
Keywords: Anti-cancer activity; bisspirooxindoles; DFT calculations; Hirshfeld surface; ultrasonication

Ultrasound-assisted ionic liquid-mediated green method for synthesis of 1,3-diphenylpyrazole-based spirooxindolopyrrolizidines, their anti-tubercular activity, molecular docking study and ADME predictions - Baddepuri, Sravanthi; Gamidi, Rama Krishna; Kumari, Jyothi; Sriram, Dharmarajan; Basavoju, Srinivas (New Journal of Chemistry, 2024)
The aim of the study is to develop the synthesis of a novel series of potent anti-tubercular (anti-TB) activity of 1,3-diphenylpyrazole-based spirooxindolopyrrolizidine derivatives via an efficient green approach achieved by using an ionic liquid ([Bmim]BF4) under ultrasonication. The title compounds 4a-4ad with a general molecular formula CaHbX(0-2)NcOd (X = F/Cl/Br) were produced with high yields in shorter reaction time and well characterized by using spectral techniques; and finally single crystal X-ray diffraction method (4b). The newly synthesized compounds were evaluated for their in vitro anti-TB activity against Mycobacterium tuberculosis H37Rv strain. Among all, six compounds 4e (C36H29N5O4), 4g (C34H28N4O3), 4q (C36H28F2N4O2), 4r (C36H28ClFN4O2), 4y (C36H29BrN4O2) and 4z (C36H28BrFN4O2) exhibited significant anti-TB activity with MIC value 6.25 mu g mL-1, when compared to the standard drug ethambutol (MIC:1.56 mu g mL-1). In silico molecular docking studies were performed against M. tuberculosis enoyl-acyl carrier protein reductase inhibitor. The compounds 4o, 4p, 4y and 4aa were exhibited least binding energies -12.58, -12.61, -12.58 and -12.57 kcal mol-1, respectively. These results reveal that the produced compounds might be used for the future generation of novel anti-TB drugs. The study aims to develop and synthesis of a novel series of 1,3-diphenylpyrazole-based spirooxindolopyrrolizidine derivatives as potent anti-TB agents via an efficient green approach by using an ionic liquid ([Bmim]BF4) under ultrasonication.

Unraveling the metal-ligand cooperativity in a phosphine-free Mn(II)-catalyzed transfer hydrogenation of nitriles to primary amines and dehydrogenation of dimethylamine borane - Chowdhury, Deep; Gupta, Kriti; Gamidi, Rama Krishna; Jindal, Garima; Mukherjee, Arup (ACS CATALYSIS, 2024)
Keywords: CATALYZED TRANSFER HYDROGENATION; STEREOSELECTIVE TRANSFER SEMIHYDROGENATION

An ultrasound-assisted green synthesis of 1,3-diphenyl pyrazole-based spirooxindolo-1,2,4-oxadiazoles: their in vitro anti-tubercular activity and in silico molecular dynamics - Baddepuri, Sravanthi; Gamidi, Rama Krishna; Kumari, Jyothi; Sriram, Dharmarajan; Gangarapu, Kiran; Basavoju, Srinivas (Chemistryselect, 2025)
A simple base-mediated one-pot synthetic green methodology has been successfully employed for the synthesis of 1,3-diphenylpyrazole-based spirooxindolo-1,2,4-oxadiazole derivatives. The newly synthesized analogues were tested for their in vitro anti-tubercular activity (anti-TB) against Mycobacterium tuberculosis H37Rv strain, and the results were reported as minimum inhibitory concentration (MIC) values ranging from 3.125 to 25 mu g/mL. Especially, the five compounds 3a, 3f, 3k, 3q, and 3v exhibited good to moderate anti-TB activity with MIC of 3.125 mu g/mL when compared to the reference drug ethambutol (MIC: 1.56 mu g/mL). In silico Molecular docking and molecular dynamics simulations of the protein-ligand complex (3a, 3f, 3k, and 3v) against Mycobacterium tuberculosis DprE1 (PDB ID: 5OEQ) of M. tuberculosis H37Rv strain revealed that these four compounds could be promising anti-mycobacterial candidates, as evident from the binding results and stability of the docked-ligand complexes with considerable least binding energies. ADME parameters were also studied to assess the drug likeness, which clearly shows that the newly developed compounds might be useful for the future development of novel anti-tubercular drugs.
Keywords: 1; 2; 4-oxadiazoles; In silico molecular dynamic studies; In vitro anti-tubercular activity; ultrasonication